2016
DOI: 10.1108/ajim-10-2015-0165
|View full text |Cite
|
Sign up to set email alerts
|

Testing the stability of “wisdom of crowds” judgments of search results over time and their similarity with the search engine rankings

Abstract: Purpose: One of the under-explored aspects in the process of user information seeking behaviour is influence of time on relevance evaluation. It has been shown in previous studies that individual users might change their assessment of search results over time. It is also known that aggregated judgments of multiple individual users can lead to correct and reliable decisions; this phenomenon is known as the "wisdom of crowds". The aim of this study is to examine whether aggregated judgments will be more stable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Even search engines struggle to produce relevancy rankings that correspond to users' relevancy judgments, so this is a very difficult challenge to address, but it may be an aspect of libraries websites to consider improving, if possible (Zhitomirsky-Geffet et al, 2016). Relevancy rankings for search results would ideally take into consideration the currency of a result as well as how closely it aligns with search terms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even search engines struggle to produce relevancy rankings that correspond to users' relevancy judgments, so this is a very difficult challenge to address, but it may be an aspect of libraries websites to consider improving, if possible (Zhitomirsky-Geffet et al, 2016). Relevancy rankings for search results would ideally take into consideration the currency of a result as well as how closely it aligns with search terms.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research in this area focuses on the relevancy of search engine results and has shown that individuals' assessments of relevancy tend to change over time. One common alternative to individual assessments of relevancy is to rely on the “wisdom of crowds” either through user studies or via click-through rates, which appears to improve the stability of relevancy judgments (Zhitomirsky-Geffet et al. , 2016; Zhitomirsky-Geffet et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there's no predicted target page, users are redirected to the irst search result of a łfeeling-luckyž background search query constrained to the present domain. Users can mark pages as correct or incorrect for the intent, and such markings are considered later by the system in selecting the target page (e.g., select the page with the most correct marks), efectively leveraging the wisdom of the crowd [74]. If users think the target page is incorrect, they can request human help ś other users of the same website ś to ind and mark the page in real time, or later when someone is online.…”
Section: User Workflowmentioning
confidence: 99%
“…Much research has focused on the issue of what strategies to undertake for sponsored results in order to achieve optimal effects (Sen, 2005; Cheng et al , 2018). Users prefer also results to be more adjusted to their expectations, or more customized, and eventually accept the changes to the displayed results (Zhitomirsky-Geffet et al , 2016). Users also tend use the search engine more when they see an interesting advertisement on the TV (Mukherjee and Jansen, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%